Some passages in the life of Mr Adam Blair, Minister of the Gospel at Cross-Meikle - Lockhart, J. G. (John Gibson), 1794-1854 (Edinburgh critical edition of the works of John Gibson Lockhart, 2020)
This edition provides the first modern publication of Lockhart's final text, the revised second edition (1824), as well as the first scholarly edition of the novel, including extensive annotations and a detailed textual history.